2021
DOI: 10.1111/jfpp.15265
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional potential and bioactive compounds of xique‐xique juice: An unconventional food plant from Semiarid Brazilian

Abstract: Xique‐xique (Pilosocereus gounellei) considered an unconventional species, is a cactus popularly consumed by local populations of Semiarid Brazilian and the cladodes are used in food preparations. The objective of this study was to elaborate juice with cladodes xique‐xique and to characterize its nutritional composition, determine the bioaccessibility of phenolic compounds, and antioxidant activity. The juice presented relevant soluble fibers (0.55 g/100 ml) and minerals contents. Nineteen phenolics compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…High ash contents have been found in xique-xique cladodes and derived juice [ 15 , 18 ], which should be linked to high contents of minerals in these products. A previous study found high contents of potassium, magnesium and calcium in xique-xique cladode juice [ 37 ]. Therefore, it could indicate that the addition of xique-xique cladode juice to the beverage formulations contributed to the higher mineral contents found in these beverages.…”
Section: Resultsmentioning
confidence: 99%
“…High ash contents have been found in xique-xique cladodes and derived juice [ 15 , 18 ], which should be linked to high contents of minerals in these products. A previous study found high contents of potassium, magnesium and calcium in xique-xique cladode juice [ 37 ]. Therefore, it could indicate that the addition of xique-xique cladode juice to the beverage formulations contributed to the higher mineral contents found in these beverages.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed that three phenolic acids (gallic, caffeic, and syringic acids) and two flavanols (epigallocatechin gallate and catechin) reached bioaccessibility values from 7% to 50%, whereas flavonoids, stilbenes, or flavonones were not detected in the dialyzed fraction. 60 In cactus pear fruit, the in vitro intestinal digestion of pulp and seeds from O. albicarpa cv. Reyna and O. ficus-indica cv.…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Aiming to take advantage of the xique-xique cladodes [45,46], elaborated and researched the mineral composition of juice, jam and yogurt using the part of the vascular cylinder of this cactacea as raw material, reporting significant mineral content.…”
Section: Mineral Profilementioning
confidence: 99%
“…According to [45], from the recommendations of the [43], consumption of 100 ml of xique-xique juice would provide 20.65% magnesium, 10.72% potassium and 2.69% calcium. The consumption of 100 ml of xique-xique juice could provide 265.22% manganese [46] observed in xiquexique jam the presence of higher concentrations of potassium, magnesium, calcium and manganese; in this case, the processing of the xique-xique cladodes resulted in higher concentrations of the minerals, which is interesting from the nutritional point of view.…”
Section: Mineral Profilementioning
confidence: 99%